GENDER STEREOTYPES OF THE PERSONALITY AND FAMILY SETTINGS IN PATIENTS WITH RESISTANT ARTERIAL HYPERTENSION - G.M. NEGMATOVA; KH.YO. SHARIPOVA; F.N. ABDULLOEV; A.A. SHERBADALOV (Avicenna Tajik State Medical University, 2017)
Objective: To study the influence of gender stereotypes of personality (GSP) and family settings (FS) on the course of arterial hypertension (AH) in middle-aged patients. Methods: One hundred sixty patients examined with AH who were under observation for at least two months after in-patient treatment. Patients divided into 2 groups: I group - 80 people (men - 34, women - 46, average age 53.2±0.45 years) with resistant hypertension; Group II - 80 patients (men - 36, women - 44, average age 53.3±0.5 years) with controlled hypertension. In all patients, GSP studied for the index staple (IS) and CS for the family settings (FS) in comparison with adherence to treatment and cardiovascular risk. Results: Frequent GSP with AH was masculine and high-masculine, revealed in 71.3% of patients with resistant and in 52.7% of patients with controlled hypertension. A moderate positive relationship between IS and FS has been established (r=0.593852, p<0.05) and a decrease in IS values to areas of masculinity and high masculinity. In a comparison of 2 groups, this combination of gender characteristics associated with a significantly low adherence to treatment (2.1±0.1 and 1.5±0.1) and a high cardiovascular risk (3.0±0.1 and 3.4±0.1), more pronounced in patients with resistant AH. It is revealed that women with gender feature indicators of the relationship characterizing the severity of the course of hypertension is much more closely related, whereas in men this relationship is insignificant. Conclusion: The combination of the masculine type of personality with traditional FS in patients with resistant hypertension accompanied by a decrease in adherence to treatment and an increase in the total cardiovascular risk, that is, it reduces the effectiveness of antihypertensive therapy and promotes the progressive course of hypertension. The identification of predictors of the decrease in the effectiveness of antihypertensive therapy, taking into account the gender characteristics of the individual and family settings, is useful for identifying a highrisk group for the development of resistant AH.